Protease Production from Bacillus sp. Isolated from Gastrointestinal Tract of Catfish (Clarias sp.) with Different Medium - Asep Awaludin Prihanto; Kartika D. Aninta; Soffi Trisnaningrum (Journal of Aquaculture and Fish Health, 2021)
The need for protease in the industrial field has been increasing. Candidates for producing these enzymes can be isolated from the digestive tract of catfish (Clarias sp.). The purpose of this study was to obtain bacterial isolates that produce proteolytic from the gastrointestinal tract of catfish and determine the effect of different production media on the activity of proteolytic. The first step of this study was isolation, screening, and identification of bacteria. The second step was to test the effect of the media Luria Bertani, trypticase soy broth, and skim milk broth on proteolytic activity. Nineteen isolates were obtained from the screening process of proteolytic bacteria. Isolate no 1, was known as the best isolate in producing enzymes and was known as Bacillus sp. Tests with different growth media gave results that semi-quantitative, nutrient growth media produced the highest activity with a proteolytic index value of 2.09 ± 0.41. In addition, based on quantitative tests, the media Luria Bertani Broth produced the highest specific activity with a value of 36.479 U/mg. The conclusion of this study, Bacillus sp. from the gastrointestinal tract of catfish that cultured on the Luria Bertani Broth medium produced the best activity.